Vibration signature analysis for monitoring rotor broken bar in double squirrel cage induction motors based on wavelet analysis. Issue 5 (26th August 2014) - Miceli, Rosario; Gritli, Yasser; Di Tommaso, Antonino; Filippetti, Fiorenzo; Rossi, Claudio
Abstract : Purpose: – The purpose of this paper is to present a diagnosis technique, for rotor broken bar in double cage induction motor, based on advanced use of wavelet transform analysis. The proposed technique is experimentally validated. Design/methodology/approach: – The proposed approach is based on a combined use of frequency sliding and wavelet transform analysis, to isolate the contribution of the rotor fault components issued from vibration signals in a single frequency band. Findings: – The proposed technique is reliable for tracking the rotor fault components over time-frequency domain. The quantitative analysis results based on this technique are the proof of its robustness. Research limitations/implications: – The validity of the proposed diagnosis approach is not limited to the analysis under steady-state operating conditions, but also for time-varying conditions where rotor fault components are spread in a wide frequency range. Practical implications: – The developed approach is best suited for automotive or high power traction systems, in which safe-operating and availability are mandatory. Originality/value: – The paper presents a diagnosis technique for rotor broken bar in double cage induction motor base on advanced use of wavelet transform which allows the extraction of the most relevant rotor fault component issued from axial vibration signal and clamping it in a single frequency bandwidth, avoiding confusions with other components and false interpretations.